Stomp and shout : R&B and the origins of Northwest rock and roll - Blecha, Peter (University of Washington Press, 2023)
"In this book, Peter Blecha tells the story of the Pacific Northwest music scene from the 1940s to the 1960s, an underappreciated golden era of music that deserves its respectful due. Drawing on extensive primary research, including his own interviews with many of the key players, Blecha weaves his own narrative voice and incisive analysis with the firsthand (and highly entertaining) stories of those who lived through the blossoming of this singular musical scene, and readers to experience the scene's evolution through the eyes and ears of those who lived through it"--